Real-time vectorcardiography simulator system - William R. Rodriguez; Hernan A. Bernal; Diana Patricia Amador-Munoz (PLoS ONE, 2026)
Vectorcardiography provides a spatial orientation and magnitude of the electrical activity of the heart, but its complexity and lack of interactive resources have limited its application in medical and bioengineering education. To bridge this pedagogical gap, we developed a low-cost, real-time vectorcardiography simulator integrating a physical wet-lab interface and digital signal processing. The hardware setup consists of a conductive medium and electrodes, enabling users to manually simulate a cardiac vector and observe the resultant electrophysiological signal consequences in real time. The system was validated through three complementary methods: theoretical conformity analysis, emulation of real ECG data from database, and user-driven waveform generation tests. A pilot study with medical students and instructors provided empirical evidence of the educational value of the device, indicating that the active, hands-on nature of the system might foster deeper cognitive engagement and facilitates the integration of complex electrophysiological concepts. By providing open-source software and cost-effective hardware, this simulator offers a scalable solution to enhance cardiac electrophysiology education and promote the broader adoption of VCG in clinical practice.